One-hour post-load plasma glucose level during the OGTT predicts dysglycemia: Observations from the 24 year follow-up of the Israel Study of Glucose Intolerance, Obesity and Hypertension. (October 2016) - Bergman, Michael; Chetrit, Angela; Roth, Jesse; Jagannathan, Ram; Sevick, Mary; Dankner, Rachel
Highlights: Early detection of those at risk is of paramount importance to prevent T2DM. The risk for diabetes associated with a 1-h level >8.6 mmol/l is increased. This is further worsened in the presence of IGT. Identifying individuals at risk with a 1-h post-load glucose level is recommended. Abstract: Aims: The present study assessed the longitudinal association of an elevated 1-h plasma glucose [1-h-PG >8.6 mmol/l (155 mg/dl)] with and without impaired glucose tolerance [IGT; 2-h-PG 7.8–11.0 mmol/l (140–199 mg/dl)] with cumulative incident of diabetes and prediabetes over 24 years in a non-diabetic cohort. Methods: From 1979 to 1984, 1970 non-diabetic men and women completed an oral glucose tolerance test (OGTT), physical and biochemical measurements as well as a questionnaire related to lifestyle and medical background. During the years 2000–2004, 853 survivors of the original cohort were interviewed and re-examined for glycemic progression. Results: Individuals with 1-h-PG >8.6 mmol/l (155 mg/dl) but with 2-h-PG <7.8 mmol/l (140 mg/dl) had a significantly elevated risk, compared to those with both 1-h-PG ⩽8.6 mmol/l (155 mg/dl) and 2-h-PG <7.8 mmol/l (140 mg/dl), for both diabetes [OR:4.35 (95%CI: 2.50–7.73)] and prediabetes outcomes [OR:1.87 (95%CI 1.09–3.26)], adjusted for sex and age, smoking, body mass index, blood pressure, fasting blood glucose and insulin. Conclusions: The risk for diabetes associated with a 1-h level >8.6 mmol/l (155 mg/dl) is increased and further worsened in the presence of IGT. Identifying individuals at risk with a 1-h-PG glucose level during an OGTT is recommended.